Computer Vision Syndrome (CVS) in Medical Students Reduced by Eye Exercise and Acupressure - Barbizu Tanamal; Naibey, Rosdiana; Sri Wadiastuti; Yulidia, Herlina; Yanti Pesurnay (Babali Publisher, 2023)
Background: A person who uses a computer continuously for 4 hours or more cause to Computer Vision Syndrome (CVS). Since the implementation of distance learning, the computer users or has increased, especially among students because learning can take place from morning to evening, so that it can have a negative impact on health, especially on eyes such as the occurrence of Computer Vision Syndrome. Research aims: to determine the prevalence and characteristics of eye disorders, namely Computer Vision Syndrome (CVS) on medical students, Papua University and to identify the effectiveness of alternative therapy by gymnastics and acupressure eyes against symptoms of Computer Vision Syndrome (CVS). Research Method: This study uses a non-equivalent control group design and then grouping into control and experimental group. Large sampling using non-probability sampling techniques with purposive sampling approach. Total sample for this research is 38 subjects. Data were collected using questionnaires and analyzed using the Wilcoxon statistical test to compare between pre-test and post-test and Mann Whitney test to compare between treatment and control groups. Results: The results of statistical analysis using Wilcoxon showed CVS scores in the experimental group after eye gymnastics and acupressure treatment was P < 0.05, while for control group with P > 0.05. Whitney Mann test experimental and control groups was showed P < 0.05. Conclusion: there are effect of Eye exercises and acupressure to reduce CVS symptoms.